Risk Factors for Breast Cancer in Undata Hospital, Palu - Gina Puspitasari; Firdaus Kunoli; Moh. Andri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
Breast cancer is the most common cancer in women, and men have a 1: 1000 chance of developing this disease. One in three people in the world will create some form of cancer in their lifetime, and in women, the most likely is breast cancer. This research is defined as an analytical study which aims to obtain an explanation of the risk factors associated with a disease. The method used was observational with a case-control approach, which is an epidemiological study design that studies the relationship between exposure and disease by comparing the case group and the control group, the sample size in the study, both cases and controls, each of 30 people. Based on the results of the study, age is a protective factor against the incidence of breast cancer at Undata Hospital Palu with an OR = 0.87 95% CI = 0.316-2.14, age of menarche is a risk factor for breast cancer with an OR = 1.52 CI 95% = 0.53-4.36, age at first gestation is a risk factor for the incidence of breast cancer in Undata Palu Hospital OR = 1.31 95% CI = 0.47-3.65, a history of breast cancer is a risk factor for the incidence of breast cancer in RSUD Undata Palu OR = 1.30 95% CI = 0.47-3.61. The hospital should cooperate with the city and provincial health offices in terms of promotion and prevention of breast cancer so that people know about breast cancer risk factors and people can carry out early detection so that breast cancer can be prevented or detected early and people living with breast cancer can be reduced by checking your breasts (BSE).